A Comparative Study on Storytelling Perceptions of Chinese, Vietnamese, American, and German Education Students. Issue 5 (3rd July 2016) - Nguyen, Kate; Stanley, Nile; Stanley, Laurel; Rank, Astrid; Wang, Yonghui
Abstract : The study compared the perceptions of adults from four countries about storytelling. Americans (N = 153), Germans (N = 163), Chinese (N = 324), and Vietnamese (N = 356) completed a survey. Americans' scores on measures of storytelling experiences were the highest overall. Americans and Germans reported having significantly more childhood experiences of storytelling than the Chinese and Vietnamese. Vietnamese reported that storytelling experiences have impacted their resilience and propensity to use storytelling for teaching more than Chinese and Germans. Practical implications are that educators should investigate their students' stance on storytelling so they may leverage culturally responsive literacy practices.